Amplitude synchronization in a system of two coupled semiconductor lasers - Lykova, O. B.; Schneider, K. R.; Yanchuk, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider a system of ordinary differential equations used to describe the dynamics of two coupled single-mode semiconductor lasers. In particular, we study solutions corresponding to the amplitude synchronization. It is shown that the set of these solutions forms a three-dimensional invariant manifold in the phase space. We study the stability of trajectories on this manifold both in the tangential direction and in the transverse direction. We establish conditions for the existence of globally asymptotically stable solutions of equations on the manifold synchronized with respect to the amplitude.